Effects of antibiotics on the life cycle of Neurospora crassa - Betina, V; Janstová, D; Spisiaková, J (Folia microbiologica, 1975)
Some antibiotics and synthetic inhibitors affect, in several ways, the life cycle of Neurospora crassa (germination of conidia leads to myceliar growth leads to formation of conidia). Bikaverin, cyanein, scopathricin and phenethyl alcohol retard the germination of conidia, without inhibiting it completely. 5-Fluorouracil, ramihyphin A and zygosporin A (cytochalasin D) do not inhibit the germination. Bikaverin brings about a thickening of the hyphae of growing mycelium. Ramihyphin A, cyanein, scopathricin and zygosporin A stimulate the ramification of hyphae while 5-fluorouracil and phenethyl alcohol do not affect the myceliar morphology apart from their inhibitory effect on growth. Actinomycin D, 5-fluorouracil, cycloheximide, ramihyphin A and partially also sodium iodoacetate inhibit to a different degree the photoinduced formation of conidia. The inhibition by 5-fluorouracil is very conspicuous when the agent is present during the photoinduction but considerably weaker when it is applied 2 h after the photoinduction.
Keywords: cyklopentany; jodacetáty; mutace; Neurospora; Cycloheximide; Phenylethyl Alcohol; vztah mezi dávkou a účinkem léčiva; Antifungal Agents; Cyclopentanes; daktinomycin; Fluorouracil; xantheny; fenethylalkohol; Ultraviolet Rays; Dactinomycin; Mutation; světelná stimulace; Photic Stimulation; cykloheximid; Cytochalasins; Dose-Response Relationship, Drug; fluoruracil; cytochalasiny; Spores, Fungal; Iodoacetates; Neurospora crassa; spory hub; antifungální látky; Xanthenes; ultrafialové záření